Oxytocin and the altruistic “Goldilocks Zone” - Roberts, Ian D. (Nat Neurosci, 2019)
When choosing whether to act altruistically, people may compare the current option to an idiosyncratic ideal. Pro-social individuals seem to represent deviations from that ideal in the amygdala, but selfish individuals do not. Oxytocin administration makes selfish individuals look more like pro-socials, behaviorally and neurally.